Development of an Integrated Lower Respiratory Tract Infection Prevention System in Head and Neck Cancer Patients - Chatchumni, Manaporn; Prasertsri, Thongdech; Pimvichai, Sirinya; Vitoonmetha, Naphatsakon (Journal of Bamrasnaradura Infectious Diseases Institute, 2026)
Lower respiratory tract infection (LRTI) is an important complication in patients with head and neck cancer. This action research with a nonrandomized two-group quasi-experimental evaluation developed and assessed an integrated LRTI prevention system in head and neck cancer wards at Maha Vajiralongkorn Thanyaburi Hospital from January to December 2023. The first 30 eligible patients received usual care (control), and the next 30 received the developed system (intervention) to minimize contamination. Four phases included: (1) situational analysis involving infection-control nurses, ward infection-control nurses, and head nurses (n = 11), plus a literature review; (2) development of online infection surveillance; (3) implementation of risk assessment, oral care, swallowing training, aspiration-prevention positioning, respiratory monitoring, and health-behavior support; and (4) outcome evaluation. Outcomes were LRTI/pneumonia, length of stay, surveillance performance, and health-promoting behavior. Appropriate t-tests or Mann–Whitney U tests and Fisher’s exact test were used. The findings showed that online surveillance improved completeness and timeliness scores (97.61 ± 10.77 vs 90.47 ± 19.87, p = .044). LRTI/pneumonia occurred in 1 intervention patient (3.3%) and 7 control patients (23.3%); the difference did not reach statistical significance (p = .052). The intervention group had a shorter hospital stay (11.70±2.10 vs 14.36±3.16 days, p = .001) and higher overall health-promoting behavior scores (177.91 ± 7.25 vs 142.39 ± 10.91, p < .001), while nutrition scores did not differ (p = .290). The integrated surveillance, risk-specific nursing bundle, and patient empowerment approach reduced length of stay and improved health behavior and may inform nursing practice in similar settings.